Efficacies of dopants in thermoelectric BiOCuSe - Chou, Ta-Lei; Tewari, Girish C.; Srivastava, Divya; Yamamoto, Atsushi; Chan, Ting-Shan; Hsu, Ying-Ya; Chen, Jin-Ming; Yamauchi, Hisao; Karppinen, Maarit (My University, 2016)
Moderately-doped BiOCuSe-based materials are actively investigated worldwide as new promising candidates for intermediate-temperature thermoelectric power generation. Here we explain for two differently doped BiOCuSe materials, i.e. Cu-deficient BiOCu1-xSe and Ca-for-Bi substituted (Bi1-yCay) OCuSe systems, the differences in their efficacies to enhance the thermoelectric performance of the pristine BiOCuSe material using theoretical calculations and x-ray absorption spectroscopy (XAS) at various edges. In the Cu-deficient system the doping dominantly induces an oxide layer-to-selenide layer charge transfer process. On the other hand, the Ca-for-Bi substitution not only gives lower electrical resistivity but also better thermal stability thanks to the increased ionic bonding character in the selenide block. Density of states nearby the Fermi level suggests that even though the Bi-Se distance is much longer than the Bi-O bond, its contribution cannot be ruled out. The Se-Bi-O chain contributes to the hole states at the VBM with the Cu 3d - Se 4p antibonding state. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Oxides; Chalcogenides; Multilayers; XAFS; Band-structure; Thermoelectric effects